Postpartum Medicaid coverage and outpatient care utilization among low-income birthing individuals in Oregon: impact of Medicaid expansion - Pradhan, Satyasandipani; Harvey, S. Marie; Bui, Linh N.; Yoon, Jangho (Frontiers in Public Health, 2023)
Objective This study examined the effect of Medicaid expansion in Oregon on duration of Medicaid enrollment and outpatient care utilization for low-income individuals during the postpartum period. Methods We linked Oregon birth certificates, Medicaid enrollment files, and claims to identify postpartum individuals (N = 73,669) who gave birth between 2011 and 2015. We created one pre-Medicaid expansion (2011–2012) and two post-expansion (2014–2015) cohorts (i.e., previously covered and newly covered by Medicaid). We used ordinary least squares and negative binomial regression models to examine changes in postpartum coverage duration and number of outpatient visits within a year of delivery for the post-expansion cohorts compared to the pre-expansion cohort. We examined monthly and overall changes in outpatient utilization during 0–2 months, 3–6 months, and 7–12 months after delivery. Results Postpartum coverage duration increased by 3.14 months and 2.78 months for the post-Medicaid expansion previously enrolled and newly enrolled cohorts (p < 0.001), respectively. Overall outpatient care utilization increased by 0.06, 0.19, and 0.34 visits per person for the previously covered cohort and 0.12, 0.13, and 0.26 visits per person for newly covered cohort during 0–2 months, 3–6 months, and 7–12 months, respectively. Monthly change in utilization increased by 0.006 (0–2 months) and 0.004 (3–6 months) visits per person for post-Medicaid previously enrolled cohort and decreased by 0.003 (0–2 months) and 0.02 (7–12 months) visits per person among newly enrolled cohort. Conclusion Medicaid expansion increased insurance coverage duration and outpatient care utilization during postpartum period in Oregon, potentially contributing to reductions in pregnancy-related mortality and morbidities among birthing individuals.